PHRASAL VERBS IN WRITTEN NARRATIVE TEXTS OF ELEVENTH GRADE OF SMAN 1 PATI - Siti Sakdidah; Ngasbun Egar; Jafar Sodiq (Wawasan Pendidikan, 2023)
Students struggle to learn to use phrasal verbs in written English. Books, writings, and social media quotes can all be used as sources. Phrasal verbs are the most common verbs in the English language. However, students must also understand the form of the phrasal verb in order to avoid making errors when writing. This study aimed to analyze the phrasal verbs in the students' written narrative texts in eleventh grade SMAN 1 Pati was used to search for the types of phrasal verbs, the errors in phrasal verbs, and solutions and suggestions from the teachers of English for students. The methods involved ranged from qualitative descriptive to document analysis. The data comes from classes XI MIPA 6, XI MIP SA7, XI IPS 1, and XI IPS 2 collecting narrative texts in pdf using a phrasal verb. The findings of this research revealed that the students' written narrative texts found types of phrasal verbs such as transitive separable, transitive non-separable, and intransitive. Then, errors in phrasal verbs include omission, addition, misformation, and misordering. The solutions and advice from the English teacher are that students should do more reading, writing, listening, and paying attention to the video lessons, memorizing the meaning and applying it in a sentence.